Multiple cotransformations in Coprinus cinereus - Ursula Kües; Michaela J Klaus; Eline Polak; Markus Aebi (Fungal Genetics Reports, 2001)
Plasmids usually integrate ectopically into the genome of the homobasidiomycete Coprinus cinereus in transformations. Often, integration occurs at multiple sites indicating that more than one plasmid copy was incorporated. This feature prompted us to study transformation with mixtures of several different plasmids in several genetic backgrounds. We found multiple cotransformation to be efficient even with four different plasmids. Simultaneous uptake of a second plasmid was between 5-55%, of two additional plasmids between 3-18% and 3% for three additional plasmids. These high frequencies make possible the analysis of interactions between different heterologous genes introduced into the same nucleus.